Geospatial modeling of near subsurface temperatures of the contiguous United States for assessment of materials degradation - Jonathan E. Gordon; Olatunde D. Akanbi; Deepa C. Bhuvanagiri; Hope E. Omodolor; Vibha Mandayam; Roger H. French; Jeffrey M. Yarus; Erika I. Barcelos (Scientific Reports)
Abstract Understanding subsurface temperature variations is crucial for assessing material degradation in underground structures. This study maps subsurface temperatures across the contiguous United States for depths from 50 to 3500 m, comparing linear interpolation, gradient boosting (LightGBM), neural networks, and a novel hybrid approach combining linear interpolation with LightGBM. Results reveal heterogeneous temperature patterns both horizontally and vertically. The hybrid model performed best achieving a root mean square error of 2.61 °C at shallow depths (50–350 m). Model performance generally decreased with depth, highlighting challenges in deep temperature prediction. State-level analyses emphasized the importance of considering local geological factors. This study provides valuable insights for designing efficient underground facilities and infrastructure, underscoring the need for depth-specific and region-specific modeling approaches in subsurface temperature assessment.